The Stifin Method As An Effort To Increase The Effectiveness Of Student Learning At Nurul Jadid Islamic Boarding School - Khalifatunnisa; Lukman Sholeh; Shabrina Ratu Alam Shufiatuddin (CV Edujavare Publishing, 2024)
The diversity that exists in the learning process is an art in teaching and learning, to observe the difference in how well students understand the subjects taught during the learning process, many tips are realized. Therefore, to produce good learning it is necessary to pay attention to several elements, one of which is the aspect of an effective learning approach. The STIFIN intelligence method is one of several effective approaches that can be used during the learning process. This approach seeks to make it easier for students to understand learning styles. The purpose of this study is to understand the learning styles of students in Al-Mawaddah Area, Nurul Jadid Paiton Islamic Boarding School, Probolinggo. This research uses a descriptive qualitative approach for several types of case studies. Data collection techniques are carried out by observation and literature review. From this research it is known that students more easily understand effective learning strategies to use during the learning process. The application can be done by starting with ice breaking to divert the attention of students to make it easier to understand the material presented. The provision of media is also very supportive in the learning process to provide support to students. Then an approach is made according to the basic machine of each student.